Contagion and Bank Failures During the Great Depression: The June 1932 Chicago Banking Panic - Calomiris, Charles W.; Mason, Joseph R. (American Economic Review, 1997)
We examine the social costs of asymmetric-information-induced bank panics in an environment without government deposit insurance. Our case study is the Chicago bank panic of June 1932. We compare the ex ante characteristics of panic failures and panic survivors. Despite temporary confusion about bank asset quality on the part of depositors during the panic, which was associated with widespread depositor runs and bank stock price declines, the panic did not produce significant social costs in terms of failures among solvent banks.